Implementation of training to improve communication with disabled children on the ward: A feasibility study. (28th May 2021) - Wilkinson, Kath; Gumm, Rebecca; Hambly, Helen; Logan, Stuart; Morris, Christopher
Abstract: Background: Parents of disabled children report poorer inpatient experiences when they stay in hospital, and some staff report finding communicating with disabled children challenging. This study tested the feasibility of implementing a training package for staff on paediatric wards to improve communication with disabled children, especially those with communication difficulties, and their families. The package was developed with parent carers and clinicians, and comprises a manual, a video of parent carers talking about real experiences, discussion points and local resources. The 50‐minutes training is intended for in‐house delivery by local facilitators. Methods: Thirteen training sessions were delivered in paediatric wards across four hospitals in England, totalling 123 staff who took part. Participants completed questionnaires before (n = 109) and after (n = 36) training, and a sample of champions (senior clinicians) and facilitators were interviewed at the end of the study. Results: Facilitators found the training easy to deliver, and participants felt they took away important messages to improve their practice. After the training, further changes were reported at an organizational level, including offering further training and reviewing practices. Conclusions: This study provides supporting evidence for the implementation of a low‐cost, minimal‐resource training package to support staff communication with children and their families in hospitals. It provides promising indication of impact on behavioural change at the individual and organizational level. Patient and public contribution: Parent carers identified the need and helped to develop the training, including featuring in the training video. They were also consulted throughout the study on research design, delivery and reporting.